2020
DOI: 10.1101/2020.03.08.983049
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Naringenin as an antibacterial reagent controlling of biofilm formation and fatty acid metabolism in MRSA

Abstract: 24MRSA is Methicillin-resistant Staphylococcus aureus and they are widespread and making 25 trouble in treatment in communities and surgical areas. MRSA have been adapted to antibiotics 26 so that they can block the access of antibiotics physically or chemically deactivate it or modify 27 the precursor of the target. Flavonoids are secondary metabolites which are naturally produced 28 by plant or fungus and they are acting generally as pigment, quorum sensing molecules, 29 antibiotics to other competitive micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…It can down-regulate the pro-inflammatory mediators, such as the intercellular adhesion molecule-1 (ICAM-1), cyclo-oxygenase-2 (COX-2), tumor necrosis factor-α (TNF-α), and interleukin-6 (IL-6) for controlling diabetes and preventing obesity via reduction of the total amount of cholesterol and triglyceride contents in plasma and liver [ 34 , 35 , 36 , 37 ]. It also shows antibacterial activity against different bacterial strains [ 19 , 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…It can down-regulate the pro-inflammatory mediators, such as the intercellular adhesion molecule-1 (ICAM-1), cyclo-oxygenase-2 (COX-2), tumor necrosis factor-α (TNF-α), and interleukin-6 (IL-6) for controlling diabetes and preventing obesity via reduction of the total amount of cholesterol and triglyceride contents in plasma and liver [ 34 , 35 , 36 , 37 ]. It also shows antibacterial activity against different bacterial strains [ 19 , 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides showing anti-cancer, cholesterol-lowering, anti-apoptotic, anti-atherogenic, anti-inflammatory and antioxidant activity, naringin is an antimicrobial agent inhibiting growth of bacteria such as Actinomyces naeslundii, Actinomyces viscosus, Aggregatibacter actinomycecomitans, Enterococcus faecalis, Escherichia coli, Staphylococcus aureus and Lactobacillus casei as well as of Candida albicans fungal species typical of the dental plaque [20]. Remarkably, naringenin (the aglycone of naringin) was lately found by scholars in South Korea to exert powerful antimicrobial activity against Methicillin-resistant Staphylococcus aureus and its mutant strain Δagr by inhibiting the microbial fatty acid synthesis [21], in full agreement with the bactericidal activity of grapefruit IntegroPectin against S. aureus lately discovered [4].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, bioflavonoid inhibited growth of both MRSA and MSSA (methicillin-sensitive S. aureus ), but the growth was visible around penicillin and oxacillin discs and methicillin strips [ 69 ]. In contrary, another study revealed synergistic interaction between naringenin and oxacillin against MRSA, resulting in lesser cell growth measured as cell density [ 70 ].…”
Section: Antimicrobial Activity Against Gram-positive Bacteriamentioning
confidence: 99%
“…Those were proven to be suppressed by this bioflavonoid [ 71 ]. An analogical study was performed for MRSA and Δ agr mutant (mutation inserted in the accessory gene regulator quorum sensing (QS) system), revealing lower expression of icaAD gene and thus lower levels of biofilm formation after incubation in naringenin [ 70 ].…”
Section: Antimicrobial Activity Against Gram-positive Bacteriamentioning
confidence: 99%
See 1 more Smart Citation